Management and use of electronic resources in selected Nigerian libraries in Ibadan, Oyo State, Nigeria (2013)
This study investigated the management and use of electronic resources in selected Nigerian libraries. Two academic and two research institute libraries were selected for the study. A descriptive survey method was adopted for the study. The instruments used for data collection were questionnaire and interview. While 450 copies of questionnaire were distributed among the respondents, 417 were retrieved and found usable. Frequency counts and simple percentages were used to analyse the data collected to give a response rate of 92.6 %. Some of the major findings of the study revealed that most library users in IITA (86.4%) make use of e-resources more often compared to users in other institutions (Lead City 44.7%>, FR1N 42.4% and U.l. 28.2%). Moreover, availability of e-resources varies across the institutions. In IITA, the e-resources were better organized and readily available to users compared to other institutions that were still restricting users’ access to some e-resources either due to inadequate equipment or unskilled personnel. Recommendations were made to promote effective management and use of e-resources such as proper funding and utilization of funds, training and re-training of both managers and users of e-resources, consideration of users’ suggestions in acquiring e-resources, and collaboration amongst libraries.